Isolation and characterization of Salt Overly Sensitive family genes in spinach. Issue 4 (16th June 2020) - Zhao, Chaoyang; William, David; Sandhu, Devinder
Abstract : The Salt Overly Sensitive (SOS) pathway regulates intracellular sodium ion homeostasis as a salt‐stress response in plants. This pathway involves three main genes designated as SOS1, SOS2 and SOS3, which are members of the Na + /H + exchanger ( NHX ), CBL‐interacting protein kinase ( CIPK ) and Calcineurin B‐like ( CBL ) gene families, respectively. To identify and characterize SOS genes in spinach ( Spinacia oleracea ), a species of the Amaranthaceae family, we conducted genome‐wide identification and phylogenetic analyses of NHX, CIPK and CBL genes from four Amaranthaceae species, Arabidopsis and rice. Most Amaranthaceae genes exhibited orthologous relationships with Arabidopsis and/or rice, except a clade of Vac‐type Amaranthaceae NHX genes. Phylogenetic analyses also revealed gene gain/loss events in Amaranthaceae species and the intron‐less to intron‐rich evolution of CIPK genes. A bacterial protein‐rooted CIPK tree allowed naming most of the phylogenetic clades based on their evolutionary history. Single S . oleracea (So) SOS1, SOS2 and SOS3 proteins were identified. Direct protein–protein interaction was observed between SoSOS2 and SoSOS3 but not between SoSOS2 and SoSOS1 based on yeast two‐hybrid assay. This may suggest distinct modes of action of spinach SOS proteins compared to Arabidopsis SOS proteins. Unlike SoSOS1 and SoSOS2, which were expressed at similar or higher levels in leaves than roots, SoSOS3 expression was significantly higher in roots than leaves, suggesting its greater importance in roots. The expression of SoSOS3 was upregulated in both roots and leaves under salinity compared to the control; however, SoSOS1 was only upregulated in roots. Thus, this study demonstrated the conservation of SOS pathway genes in spinach and also highlighted the complexity of SOS signaling in Amaranthaceae species.